Ethical dilemmas of youth participatory action research in a democratic setting. Issue 3 (4th March 2017) - Mitra, Dana; McCormick, Paul
ABSTRACT: This article discusses ethical issues involved in facilitating the research of young people on controversial issues. This article considers the potential ethical dilemmas of teachers facilitating a particular form of activism – youth participatory action research (YPAR). We consider how teachers foster school-wide conversations on difficult issues and support students who wish to take a critical stand on issues of race, class and gender. The article also discusses how to scaffold the exploration of topics that require emotional maturity and might lead to shifts in beliefs that run counter to the values of one's family.